Bagaimana Teknologi Informasi dan Komunikasi Bertransformasi Menjadi Inovasi Pelayanan Publik? - Fadian Nur Aziz; Fathum Mubin; Rizky Juda Putra Hidayat; Asep Nurjaman; Achmad Apriyanto Romadhan; Tri Sulistyaningsih; Yana Syafriyana Hijri (Universitas Medan Area, 2021)
This study aims to analyze how ICT can change the mechanism of public service innovation and see the success indicators, with an empirical study on the Among Warga application in Batu City. Basically, ICT is a technology that can help reduce government performance, thus making a demand for the dynamics of public service delivery at the regional level. The method used in this research is a qualitative paragraph with a descriptive model in which the researcher looks for key informants or data sources based on facts in the field, and is supported by literature studies.. Referring to the results of the data that have been processed, the researchers found research results that show that the Among Warga application is an online-based complaint service facility which is shown for the people of Batu City in submitting public complaints such as infrastructure damage, fallen trees and natural disasters. However, the Among Warga application's journey has stopped for only one year since it was created in 2017. Meanwhile, the Batu City government is not ready to take advantage of ICT, this is due to the absence of innovative organizational capacity and transformational leadership. Therefore, in this study the authors would like to provide advice to government organizations in building ICT-based innovation concepts, the government is not a single actor, but requires cooperation with the private sector and participation from the community as an indicator..